2016
DOI: 10.1590/0102-6720201600s10013
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electromyography of Masseter and Temporal Muscles With Use Percentage While Chewing on Candidates for Gastroplasty

Abstract: Background:Surface electromyography identifies changes in the electrical potential of the muscles during each contraction. The percentage of use is a way to treat values enabling comparison between groups. Aim:To analyze the electrical activity and the percentage of use of masseter and temporal muscles during chewing in candidates for gastric bypass. Methods:It was used Surface Electromyography Miotool 200,400 (Miotec (r), Porto Alegre/RS, Brazil) integrated with Miograph 2.0 software, involving patients betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…These results are in agreement with the study by Santos et al, 22 where the electrical activity of the masseter and temporalis muscles was analyzed in a voluntary maximal intercuspal squeeze in a group of obese candidates for gastroplasty in Brazil, it was observed that the left temporalis muscle presented a higher percentage of electrical activity than the right one. Furthermore, they are related to the results reported by Figueiredo et al, 23 who had already reported that in obese women, the electrical activity of the temporalis muscle presented certain asymmetries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with the study by Santos et al, 22 where the electrical activity of the masseter and temporalis muscles was analyzed in a voluntary maximal intercuspal squeeze in a group of obese candidates for gastroplasty in Brazil, it was observed that the left temporalis muscle presented a higher percentage of electrical activity than the right one. Furthermore, they are related to the results reported by Figueiredo et al, 23 who had already reported that in obese women, the electrical activity of the temporalis muscle presented certain asymmetries.…”
Section: Discussionsupporting
confidence: 93%
“…Material y Métodos: Se realizó un estudio observacional de corte transversal con una muestra de 21 participantes con una edad promedio de 22.9 ± 3.5 años, quienes fueron clasificados de acuerdo a su índice de masa corporal, formando tres grupos de estudio: peso normal (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)9), sobrepeso (25,9) y obesidad (≥30.0), con siete participantes cada uno. La electromiografía de superficie evaluó los músculos superficiales de la masticación durante la fuerza de mordida máxima derecha e izquierda.…”
Section: Introductionunclassified
“…The purpose of the rest was to analyze the quality of the signal and that of the MVC was to standardize the signal. In both, three collections were made in each situation, with an approximate 1-minute rest for muscle recovery in between collections 34 . The collection with the best signal quality of the three was chosen, according to the Fast Fourier Transform (FFT) frequency spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…O potencial de ação gerado durante a contração muscular é captado pelos eletrodos na superfície da pele, na região do grupo muscular desejado 11 . Alguns testes realizados mostraram que o sistema de comunicação assistiva em questão tem grande potencial para o auxílio de usuários que não conseguem se comunicar devido a disfunções motoras graves e perda da fala 12,13 . A necessidade de recursos de adaptação, implica na necessidade de saber sobre o quadro motor e ferramentas de baixo e alto custo que proporcionem a adaptação 14 .…”
Section: Métodounclassified